Antibody Delivery Mediated by Recombinant Adeno-associated Virus for the Treatment of Various Chronic and Infectious Diseases - Robert, Marc-André; Gilbert, Rénald; Gaillet, Bruno (Current Gene Therapy, 2016)
Monoclonal antibodies (mAbs) based-therapies are currently one of the most successful strategies to treat immune disorders, cancer and infectious diseases. Vectors derived from adenoassociated virus (AAV) are very attractive to deliver the genes coding the mAbs because they allow long-term expression thus, reducing the number of administrations. They can also penetrate biological barriers such as the blood-brain-barrier to transduce cells localized in immunoprivileged organs. Recent animal studies with AAV have demonstrated the capacity of AAV to deliver sufficient quantity of antibodies to confer an efficient immunoprotection against chronic and infectious diseases for several months to years. The treatment was successfully applied either for prophylaxis or therapeutic use, depending on the disease and its progression. In this review, we discuss the advantages and the limitations of AAV for mAb and immunoadhesin delivery. Recent advances in vector design and antibody engineering are also presented. Optimization of the vector design can improve the kinetic and the level of mAbs expression whereas protein engineering can enhance transgene product properties. Furthermore, an exhaustive review of pre-clinical studies for chronic diseases including Alzheimer disease, amyotrophic lateral sclerosis and cancer is presented as well as for infectious diseases.
Keywords: Recombinant adeno-associated virus